PENINGKATAN KEMAMPUAN GURU MATEMATIKA DALAM PERANCANGAN SOAL-SOAL BERBASIS HOTS PADA PELAKSANAAN SUPAK MELALUI TEKNIK PENDAMPINGAN PENGAWAS SEKOLAH SECARA BERKALA PADA MGMP MATEMATIKA KOTA BENGKULU TAHUN PELAJARAN 2016/2017 - Rahmad Ramelan Setia Budi; Junaini Junaini (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2018)
The purpose of this research are: (1) to describe the planning of academic supervision by supervising school supervisory technique periodically at Mathematics Teacher Organization of Bengkulu City to improve the ability of math teacher in designing HOTS-based questions; (2) to describe the implementation of academic supervision by regular supervision of school supervisor at Mathematics Teacher Organization of Bengkulu City to improve the ability of mathematics teacher in designing HOTS-based questions; (3) to describe the evaluation of academic supervision by regular supervision of school supervisors at Mathematics Teacher Organization of Bengkulu City to improve the ability of math teachers in HOTS-based problem-solving; (4) to describe the supporting factors and factors inhibiting the implementation of academic supervision by regular supervision of school supervisors in Mathematics Teacher Organization of Bengkulu City to improve the ability of math teachers in the design of HOTS-based questions; and (5) to describe solution or effort to overcome the obstacle factor of the implementation of academic supervision by regular supervision of school supervisor on Mathematics Teacher Organization of Bengkulu City to improve the ability of math teacher in designing HOTS based problems. The research method used to examine the problem is qualitative descriptive method. This qualitative research procedure follows a research procedure that produces descriptive data in the form of written or oral words of persons and observable behavior. Research Sites at Mathematics Teacher Organization of Bengkulu City based in Senior High School of Vocational State Number 2 in Bengkulu city. In this study, the subjects studied were the active members of Mathematics Teacher Organization of Bengkulu City, which amounted to about 20 of mathematics teachers of Senior High School of Vocational subjects throughout the city of Bengkulu. Based on the results of the study and discussion focused it can be concluded that the technical supervision of school supervisors on a regular basis in Mathematics Teacher Organization of Bengkulu City was able to improve the ability of math teachers in designing problems based on HOTS in the school year 2016/2017. With the technical supervision of school supervisors on a regular basis at the Mathematics Teacher Organization of Bengkulu City was able to contribute to improving the ability of math teachers in designing HOTS-based questions according to rules and procedures required.